Numerical Evaluation of Structural Performance in Modular Mechanical Assemblies (Strojniški vestnik – Journal of Mechanical Engineering, 2015)
This paper evaluates the structural performance of modular mechanical assemblies subjected to complex loading conditions. Numerical simulations were conducted to investigate stress distribution, deformation behavior, and load-bearing capacity. The results demonstrate that optimized structural configurations effectively improve assembly reliability and operational efficiency in industrial applications.
Keywords: Modular assemblies; Structural performance; Finite element analysis; Mechanical design; Reliability